Transparência nos pequenos municípios do Rio Grande do Sul: um estudo sobre a divulgação de indicadores da LRF e da LAI - Marques, Simone Beatriz Santos da Silva (Universidade do Vale do Rio dos Sinos, 2014)
In this research we analyze the existence in the electronic pages of the City Hall of the municipalities in the Rio Grande do Sul State, whose population number floats in between ten, thousand and fifty thousand inhabitants to find indicators demanded by the Fiscal Responsibility Law and the Information Access Law . The research is classified as applied, with a quantitative approach of data, descriptive in its objectives and documentary in the relation to the technical procedure counting on a sample of 94 municipalities. Altogether was examined the disclosure of 32 indicators, 16 refer to the LRF and 16 refer to the LAI. The analysis considered the frequency of the disclosure and the influences in the factors disclosure such as: population, net current income, per capita Gross National Product, Human Development index and illiteracy rate. The obtained data reveal a low medium adherence of governments in disseminating indicators of LRF the City Hall over the LRF disclosure indicators and a little bit more satisfactory adherence of the City Hall related to LAI indicators disclosure and that the municipalities population influences the major or minor evidence; the amount of the net current income has a moderate influence and there is no difference in the LRF and LAI indicators disclosure levels in the municipalities with major or minor per capita GNP, HDR and illiteracy rate.
Keywords: Transparência no setor público; Lei de responsabilidade fiscal; Lei de acesso à informação; Public sector transparency; Fiscal responsibility law; Information access law; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis